2014
DOI: 10.1038/ncomms5601
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor Y-mediated H3K27me3 demethylation of the SOC1 locus orchestrates flowering responses of Arabidopsis

Abstract: Nuclear factor Y (NF-Y) is a conserved heterotrimeric transcription factor complex that binds to the CCAAT motifs within the promoter region of many genes. In plants, a large number of genes code for variants of each NF-YA, B or C subunit that can assemble in a combinatorial fashion. Here, we report the discovery of an Arabidopsis NF-Y complex that exerts epigenetic control over flowering time by integrating environmental and developmental signals. We show that NF-Y interacts with CONSTANS in the photoperiod p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
257
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(277 citation statements)
references
References 72 publications
(113 reference statements)
18
257
1
1
Order By: Relevance
“…The yeast three-hybrid analysis indicated that a H2A/H2B dimer is selective for NF-YA subunits, although the NF-YA subunits are highly similar to each other in Arabidopsis ( Figure 8D). A previous study suggested that the NF-YB6/NF-YC3 dimer did not form a trimer with NF-YA2 , although a recent study indicated that the NF-YB3/NF-YC9 dimer formed a trimer with NF-YA2 (Hou et al, 2014). Additionally, among the H2B-like proteins, DPB4, NC2b1, and NC2b2 did not form trimers with DPB3-1 and (E) Transactivation of the HsfA3 1-kb promoter:GUS reporter gene by various combinations of trimers and DREB2A CA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast three-hybrid analysis indicated that a H2A/H2B dimer is selective for NF-YA subunits, although the NF-YA subunits are highly similar to each other in Arabidopsis ( Figure 8D). A previous study suggested that the NF-YB6/NF-YC3 dimer did not form a trimer with NF-YA2 , although a recent study indicated that the NF-YB3/NF-YC9 dimer formed a trimer with NF-YA2 (Hou et al, 2014). Additionally, among the H2B-like proteins, DPB4, NC2b1, and NC2b2 did not form trimers with DPB3-1 and (E) Transactivation of the HsfA3 1-kb promoter:GUS reporter gene by various combinations of trimers and DREB2A CA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NF-Y trimers have been suggested to act in concert with a histone acetyltransferase (Li et al, 1998;Caretti et al, 2003;Peng et al, 2007), affecting the acetylation of histone H2A.Z on promoters (Li et al, 1998;Caretti et al, 2003;Peng et al, 2007;Gatta and Mantovani, 2011). Moreover, a recent study revealed that a NF-Y trimer is also involved in histone methylation to regulate the target gene expression of a transcription factor (Hou et al, 2014). Therefore, further study is required to reveal the regulation of histone modifications during drought or heat stress responses.…”
Section: Nf-ya (mentioning
confidence: 99%
“…NF-Y subunits interact with other transcription factors to modulate gene expression in plant development and stress responses (Liu and Howell, 2010;Hou et al, 2014). LEC1 belongs to the NF-YB family; thus, we reasoned that LEC1 might function with other partners in the regulation of hypocotyl elongation during postembryonic development.…”
Section: Lec1 Interacts With Pif4mentioning
confidence: 99%
“…Full-length cDNAs of LEC1 and PIF4 were cloned into the pGreen binary vector HY105 containing C-or N-terminal fusions of EYFP to generate 35S: LEC1-EYFP C and 35S:PIF4-EYFP N , then cotransformed into tobacco (Nicotiana benthamiana) leaf epidermal cells by infiltration as previously published (Hou et al, 2014). After infiltration, tobacco was grown for 2 d and transferred to darkness for 24 h before detection of the YFP signals.…”
Section: Bifc Assaymentioning
confidence: 99%
See 1 more Smart Citation